2017
DOI: 10.1021/acs.est.7b02861
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence State and Molecular Structure Analysis of Extracellular Proteins with Implications on the Dewaterability of Waste-Activated Sludge

Abstract: The occurrence state and molecular structure of extracellular proteins were analyzed to reveal the influencing factors on the water-holding capacities of protein-like substances in waste-activated sludge (WAS). The gelation process of extracellular proteins verified that advanced oxidation processes (AOPs) for WAS dewaterability improvement eliminated the water affinity of extracellular proteins and prevented these macromolecules from forming stable colloidal aggregates. Isobaric tags for relative and absolute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(23 citation statements)
references
References 61 publications
2
21
0
Order By: Relevance
“…extracellular proteins was considered more important in holding bound water, as they comprise the major hydrophilic groups in the sludge (Wu et al, 2017).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…extracellular proteins was considered more important in holding bound water, as they comprise the major hydrophilic groups in the sludge (Wu et al, 2017).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…EPS consists of high hydrophilic substances, and those substances mainly include proteins and polysaccharides. Moreover, protein played more important role in sludge dewaterability than polysaccharides (Wu, Zhang, et al, 2017;Wu, Ni, et al, 2017). The influence of NaIO 4 concentration and initial pH on the properties of different EPS fractions is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Some advanced sludge treatment processes, such as heat hydrolysis and acid/alkaline treatment, have been developed to improve sludge dewatering efficiency (Guan et al, 2012). In addition, chemical oxidation (Wu et al, 2015), such as the Fenton reaction and potassium permanganate (Wu, Zhang, et al, 2017;Wu, Ni, et al, 2017), has been reported as an effective approach to solubilize EPS. Fenton's oxidation process utilizes Fe (II) to activate H 2 O 2 , generating hydroxyl radicals, which can oxidize proteins and polysaccharides and destroy the connections between EPS and water.…”
Section: Introductionmentioning
confidence: 99%
“…bound water) and stabilized microbial aggregation colloid. [6][7][8] That cannot full the disposal requirements of sludge landll and incineration (i.e. DS more than 40% and 50% respectively, in China standard GB/T 23485-2009 and GB/T 24602-2009).…”
Section: Introductionmentioning
confidence: 99%